Divalent iron-containing catalyst, preparation method and application thereof, and method for producing nitrile compounds through low-carbon olefin ammoxidation reaction

By introducing a divalent iron phase into the catalyst, the problem of insufficient conversion and selectivity of existing catalysts in the acrylic ammonia oxidation reaction is solved, and more efficient acrylonitrile production is achieved.

CN119701988AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311280636.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
2043-09-28

AI Technical Summary

Technical Problem

In the ammonia oxidation reaction of existing ammonia oxidation catalysts, the propylene conversion and acrylonitrile yield are relatively low.

Method used

A catalyst containing divalent iron is used, which consists of a support and an active component, the general formula of active component is Mo11.0 BibFecDdEeFfOx, which is prepared by co-precipitation method, and the pH value is adjusted during the preparation process to ensure that the divalent iron phase exists in the catalyst.

Benefits of technology

The conversion rate of the ammonia oxidation reaction and the selectivity of the target product are improved, especially in the ammonia oxidation reaction of low-carbon olefins, which significantly improves the yield of acrylonitrile.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701988A_ABST
    Figure CN119701988A_ABST
Patent Text Reader

Abstract

The invention relates to a divalent iron-containing catalyst, a preparation method and an application thereof, and a method for producing nitrile compounds through low-carbon olefin ammoxidation, the catalyst comprises a carrier and an active component represented by the following general formula: Mo11.0 BibFecDdEeFfOx, in the formula, D is selected from at least one of Li, Na, K, Rb and Cs; e is selected from at least one of rare earth elements La, Pr, Nd, Sm and Eu; f is selected from at least one of Ca, Mg, Zr, Te, Sb, Ni, Cr, W and Nb; wherein the value range of b is 0.1 to 5.0; the value range of c is 0.1 to 5.0; the value range of d is 0.1 to 5.0; the value range of e is 0.1 to 5.0; the value range of f is 0.1 to 15.0; x is the total number of oxygen atoms required for meeting the valence of each element in the catalyst; a divalent iron phase exists in the crystal structure of the catalyst. The catalyst is applied to preparation of acrylonitrile through propylene ammoxidation, and has the characteristics of high propylene conversion rate and high acrylonitrile selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a catalyst containing divalent iron, a preparation method and application thereof, and a method for producing nitrile compounds by ammoxidation of low-carbon olefins. Background Art

[0002] At present, the industrial production of propylene ammoxidation to prepare unsaturated nitrile generally adopts fluidized bed ammoxidation process. As one of the core technologies of this process, the catalyst has been paid attention to in research and improvement. There are two main types of catalysts for industrial propylene ammoxidation to acrylonitrile: Mo-Bi series and Sb series. Among them, Mo-Bi series catalysts dominate, accounting for 95% of the olefin ammoxidation market. Previous research and exploration also mainly focused on Mo-Bi series catalysts.

[0003] The activity of the catalyst can be improved by introducing metal components with variable valence states, such as Fe, Ce and other elements into the catalyst. By introducing metal elements with ion radius greater than 0.8nm and less than 0.8nm, such as Cr, Ni, Mg, Mn, Zn, Al and other elements, they play the role of structural and electronic additives and improve the structure and stability of the catalyst. By introducing rare earth elements, the amount of lattice oxygen in the catalyst can be increased and the catalytic performance of the catalyst can be improved. By introducing elements such as Cs, Rb, P, B, Al, the surface of the catalyst can be modified and the acidity and alkalinity can be adjusted to improve the selectivity and activity of the catalyst.

[0004] US 8455388 reported a Mo containing Ce element 12 Bi a Fe b A c D d E e F f G g Ce hOx compound, wherein A is at least one of sodium, potassium, rubidium and cesium; D is at least one of nickel, cobalt, magnesium, zinc, manganese, calcium, strontium, cadmium and barium; E is at least one of chromium, tungsten, boron, aluminum, gallium, indium, phosphorus, arsenic, antimony, vanadium and tellurium; F is at least one of titanium, zirconium, hafnium, niobium, tantalum, thallium and germanium; G is at least one of silver, gold, ruthenium, rhodium, palladium, osmium, iridium, platinum and mercury. The ratio of each atom is limited to 0.05≤a≤7, 0.1≤b≤7, 0.01≤c≤5, 0.1≤d≤12, 0≤e≤5, 0≤f≤5, 0≤g≤0.2, 0.01≤h≤5, wherein 0.15≤(a+h) / d≤1, 0.8≤h / b≤5. The diffraction peak intensity of 2θ=28±0.3° in the XRD spectrum is selected as X, and the diffraction peak intensity of 2θ=26.5±0.3° is selected as Y, and the X / Y ratio is equal to or greater than 0.7. When 0.2≤(a+h) / d≤0.6, 1≤h / b≤3, the X / Y ratio is equal to or greater than 0.8, and when 0.3≤(a+h) / d≤0.5, 1.5≤h / b≤2, the X / Y ratio is equal to or greater than 0.9. It only explains that the catalyst contains Fe element, but does not provide a detailed description of the physical phase in which Fe exists. Summary of the invention

[0005] The technical problem to be solved by the present invention is to improve the raw material conversion rate and target product selectivity of an ammonia oxidation catalyst.

[0006] It is generally believed that Fe exists mainly in the form of ferric molybdate Fe2(MoO4)3 in the fresh Mo-Bi catalyst after calcination. During the oxidation-reduction reaction, Fe2(MoO4)3 will be reduced to ferrous molybdate FeMoO4 by the reducing raw material, and then FeMoO4 will be oxidized to Fe2(MoO4)3 by air supplementation. 3+ / Fe 2+ The presence of electron pairs plays an important role in promoting the rapid migration of oxide lattice oxygen. However, the present invention has found through research that the difficulty of FeMoO4 phase formation in the oxidation-reduction cycle, Fe 3+ / Fe 2+ The number of electron pairs will have an important impact on the oxygen migration ability of the oxide lattice, the activity and stability of the catalyst.

[0007] According to a first aspect of the present invention, the present invention provides a catalyst containing divalent iron, the catalyst comprising a carrier and an active component represented by the following general formula:

[0008] Mo 11.0 Bi b Fe c D d E e F f O x,

[0009] wherein D is selected from at least one of Li, Na, K, Rb and Cs;

[0010] E is at least one selected from the group consisting of rare earth elements La, Pr, Nd, Sm and Eu;

[0011] F is selected from at least one of Ca, Mg, Zr, Te, Sb, Ni, Cr, W and Nb;

[0012] in,

[0013] The value range of b is 0.1~5.0; the value range of c is 0.1~5.0; the value range of d is 0.1~5.0; the value range of e is 0.1~5.0; the value range of f is 0.1~15.0; x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst; there is a divalent iron phase in the catalyst crystal structure.

[0014] According to a second aspect of the present invention, the present invention provides a method for preparing the divalent iron-containing catalyst of the present invention, the method comprising:

[0015] (a) dissolving a Mo source to obtain a molybdenum-containing solution I;

[0016] (b) dissolving the Fe source, the organic acid additive and the E source to obtain an iron-containing solution II;

[0017] (c) dissolving the remaining active component sources to obtain active component solution III;

[0018] (d) mixing a required amount of carrier source with molybdenum-containing solution I and dividing the mixture into two parts by volume, labeled as molybdenum-containing solution I′ and molybdenum-containing solution I″;

[0019] (e) mixing the iron-containing solution II with the molybdenum-carrying solution I' to form a coprecipitation slurry II', and adjusting the pH value thereof to 1.0-8.0 with an alkaline substance; mixing the active component solution III with the molybdenum-carrying solution I'' to form a coprecipitation slurry III';

[0020] (f) The coprecipitation slurry II′ and the coprecipitation slurry III′ are then mixed and aged, and then dried and calcined to obtain a catalyst.

[0021] According to the third aspect of the present invention, the present invention provides the use of the catalyst of the present invention in an ammoxidation reaction, preferably in an ammoxidation reaction of a low-carbon olefin, and more preferably the low-carbon olefin is propylene and / or isobutylene.

[0022] According to a fourth aspect of the present invention, the present invention provides a method for producing nitrile compounds by ammoxidation of light olefins, the method comprising: carrying out an ammoxidation reaction of light olefins, ammonia and air as raw materials.

[0023] The coexistence of divalent iron phase and trivalent iron phase in the catalyst of the present invention is conducive to the rapid migration of lattice oxygen at a relatively low reaction temperature, so that the catalyst has better reaction performance, especially better ammoxidation reaction performance, especially the reaction performance of ammoxidation of light olefins.

[0024] The technical key of the present invention is to use raw materials of Fe source and organic acid auxiliary agent in combination with other technologies of the present invention in the catalyst preparation process, and to use the co-precipitation method of the present invention and adjust its pH value. Compared with directly using nitrate iron raw material and the slurry without pH adjustment, the catalyst is characterized by oxygen programmed temperature oxidation (i.e., O2-TPO) after calcination, and an oxygen consumption peak is detected, indicating that there are low-valent compounds that can be oxidized in the catalyst, and XRD is used to detect the presence of a divalent iron phase in the crystal structure.

[0025] The present invention can well solve the problem of low propylene conversion rate and acrylonitrile yield of catalysts for ammoxidation, such as propylene ammoxidation to acrylonitrile in the prior art. The catalyst of the present invention is applied to ammoxidation to nitrile and has the characteristics of high conversion rate and nitrile selectivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is the XRD pattern of Example 1;

[0027] Figure 2 It is the O2-TPO diagram of Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0028] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0029] The present invention provides a catalyst containing divalent iron, which comprises a carrier and an active component represented by the following general formula:

[0030] Mo 11.0 Bi b Fe c D d E e F f O x ,

[0031] wherein D is selected from at least one of Li, Na, K, Rb and Cs;

[0032] E is at least one selected from the group consisting of rare earth elements La, Pr, Nd, Sm and Eu;

[0033] F is selected from at least one of Ca, Mg, Zr, Te, Sb, Ni, Cr, W and Nb;

[0034] in,

[0035] The value range of b is 0.1~5.0; the value range of c is 0.1~5.0; the value range of d is 0.1~5.0; the value range of e is 0.1~5.0; the value range of f is 0.1~15.0; x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst; a divalent iron phase exists in the crystal structure of the catalyst.

[0036] After the catalyst of the present invention is calcined, XRD detection is performed and a divalent iron phase is found in the crystal structure.

[0037] In the present invention, the optional range of the content of the carrier and the active component is relatively wide, and the commonly used content ranges can be used in the present invention. For the present invention, it is preferred that the carrier accounts for 30-65% of the catalyst weight, and the active component accounts for 35-70% of the catalyst weight, calculated as oxide.

[0038] The catalyst of the present invention contains low-valent compounds that can be oxidized, that is, the catalyst is calcined at high temperature and then subjected to oxygen temperature-programmed oxidation (ie, O2-TPO characterization) to detect the presence of low-valent compounds that can be oxidized.

[0039] In the present invention, there is no special requirement for the preparation method of the catalyst. As long as the catalyst having the above characteristics can be prepared, the purpose of the present invention can be achieved. According to a preferred embodiment of the present invention, a preparation method of the catalyst containing divalent iron is provided, which comprises:

[0040] (a) dissolving a Mo source to obtain a molybdenum-containing solution I;

[0041] (b) dissolving the Fe source, the organic acid additive and the E source to obtain an iron-containing solution II;

[0042] (c) dissolving the remaining active component sources to obtain active component solution III;

[0043] (d) mixing a required amount of carrier source with molybdenum-containing solution I and dividing the mixture into two parts by volume, labeled as molybdenum-containing solution I′ and molybdenum-containing solution I″;

[0044] (e) mixing the iron-containing solution II with the molybdenum-carrying solution I' to form a coprecipitation slurry II', and controlling the pH value of the coprecipitation slurry II' to be between 1.0 and 8.0; mixing the active component solution III with the molybdenum-carrying solution I'' to form a coprecipitation slurry III';

[0045] (f) The coprecipitation slurry II′ and the coprecipitation slurry III′ are then mixed and aged, and then dried and calcined to obtain a catalyst.

[0046] In the present invention, the Fe element is used in a timely manner in the preparation process of the catalyst by using a Fe source and an organic acid additive as raw materials through a coprecipitation method.

[0047] In the present invention, the dissolution is heated as required to achieve the purpose of dissolution, which is well known to those skilled in the art and will not be described in detail in the present invention.

[0048] The technical key of the present invention is to use Fe source and organic acid additive as raw materials in the catalyst preparation process, cooperate with other technologies of the present invention, adopt coprecipitation method and adjust its pH value, etc., compared with the iron raw material directly using nitrate, the slurry is not pH-adjusted, the catalyst is characterized by oxygen temperature programmed oxidation (i.e. O2-TPO) after roasting, and the presence of oxidizable reducing compounds in the catalyst is detected, and the presence of divalent iron phase in the crystal structure is detected by XRD. The coexistence of divalent iron phase and trivalent iron phase in the catalyst is conducive to the rapid migration of lattice oxygen at a lower reaction temperature, so that the catalyst has better reaction performance.

[0049] In the present invention, the volume ratio of the molybdenum-carrying solution I′ to the molybdenum-carrying solution I″ can be selected in a wide range. For the present invention, the preferred volume ratio of the molybdenum-carrying solution I′ to the molybdenum-carrying solution I″ is 1:0.5-5, preferably 1:1-3. Dividing the molybdenum-carrying solution into two parts can achieve batch co-precipitation with the iron-containing solution II and solution III.

[0050] In the present invention, the optional range of types of organic acid additives is relatively wide, and the following exemplary description is given, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the organic acid additive is one or more of tartaric acid, citric acid, and oxalic acid, preferably oxalic acid, and more preferably oxalic acid dihydrate.

[0051] In the present invention, the optional range of the amount of the organic acid additive is relatively wide, which is exemplified below, but the scope of the present invention is not limited thereto. According to a preferred embodiment of the present invention, the molar ratio of the organic acid additive to the Fe ion in the iron source is 0.5-5.0, preferably 1.0-2.5, including but not limited to 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, etc.

[0052] In the present invention, the Fe source has a wide range of options, and commonly used Fe sources can achieve the purpose of the present invention. For the present invention, ferric nitrate, ferric sulfate, and ferric citrate are preferred, and ferric citrate is preferred.

[0053] In the present invention, the alkaline substance has a wide range of options, and commonly used alkaline substances can achieve the purpose of the present invention. For the present invention, the alkaline substance is preferably an inorganic base, such as one or more of potassium hydroxide, sodium hydroxide, and ammonia water, and ammonia water is particularly preferred.

[0054] In the present invention, the pH value of the coprecipitation slurry II' is preferably 3.0 to 7.0, including but not limited to 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, etc. This can further improve the performance of the catalyst.

[0055] In the present invention, the range of aging conditions is relatively wide. In the present invention, in the preferred step (f), the aging conditions include: a temperature of 40 to 150°C, preferably 50 to 120°C, and preferably 80 to 100°C.

[0056] According to the present invention, in the preferred step (f), the aging conditions include: a time of 10 minutes to 10.0 hours, preferably 30 minutes to 5 hours, preferably 1 to 3 hours.

[0057] In the present invention, the drying conditions can be selected in a wide range, and commonly used drying methods and steps are applicable to the present invention. For the present invention, in the preferred step (f), the oven drying conditions include: a temperature of 80 to 160°C, preferably 90 to 150°C.

[0058] For the present invention, the drying time is determined as needed. The following exemplary description is not limited to the scope of the present invention. For the present invention, in the preferred step (f), the oven drying conditions include: the time is 5.0 to 24.0 hours, preferably 8.0 to 12.0 hours.

[0059] In the present invention, the range of roasting conditions is relatively wide, and commonly used roasting conditions can be used in the present invention. For the present invention, in the preferred step (f), the roasting conditions include: the roasting environment adopts an air atmosphere, or a mixed atmosphere of a trace amount of reducing gas and air. Preferably, the volume percentage of the reducing gas in the mixed atmosphere is 0.01 to 3.0%, preferably 0.5 to 2.5%. There are many types of reducing gases. In the present invention, ammonia is used as an example to illustrate the advantages of the present invention.

[0060] In the present invention, the calcination temperature can be selected in a wide range. For the present invention, the preferred calcination temperature is 550-650°C.

[0061] In the present invention, the calcination time is determined according to needs. For the present invention, the calcination time is 0.5 to 2.5 hours.

[0062] In the present invention, there is no special requirement for the concentration of each solution. The preferred embodiments of the present invention are described below, but the scope of the present invention is not limited thereby.

[0063] For the present invention, the Mo concentration of the molybdenum-containing solution I is preferably 2.0-8.0 mol / L, preferably 2.5-5.5 mol / L, including but not limited to 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, 4.2, 4.4, 4.6, 4.8, 5.0, 5.2, 5.4 mol / L, etc.

[0064] According to the present invention, the total metal ion concentration of the iron-containing solution II is preferably 1.0 to 5.0 mol / L, preferably 2.5 to 4.2 mol / L, including but not limited to 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0 mol / L, etc.

[0065] According to the present invention, the total metal ion concentration of the active component solution III is preferably 3.0 to 14.0 mol / L, preferably 4.0 to 6.0 mol / L.

[0066] In the present invention, there is a wide range of carrier sources to choose from, and commonly used carrier sources can be used in the present invention. The following describes the preferred embodiments of the present invention, but does not limit the scope of the present invention.

[0067] For the present invention, the preferred carrier source is selected from silica sol, preferably a silica sol having a silica weight content of 25-50%, preferably 30-40%, for example a silica sol having a silica content of 30%, 40% or 45%.

[0068] The present invention provides use of the catalyst of the present invention in an ammoxidation reaction, preferably in an ammoxidation reaction of a low-carbon olefin, and more preferably the low-carbon olefin is propylene and / or isobutylene.

[0069] The present invention provides a method for producing nitrile compounds by ammoxidation of light olefins, the method comprising: carrying out an ammoxidation reaction using light olefins, ammonia and air as raw materials; in the present invention, the optional range of reaction conditions is relatively wide, and commonly used reaction conditions can be used in the present invention. The preferred embodiments of the present invention are described below, but the scope of the present invention is not limited thereby.

[0070] According to the present invention, the preferred raw material molar ratio is: propylene / ammonia / air = 1: (1.05-1.3): (9.2-9.8).

[0071] According to the present invention, the preferred reaction temperature is 420-440°C.

[0072] According to the present invention, the preferred reaction pressure is 0 to 0.14 MPa.

[0073] For the present invention, the catalyst preferably has an olefin feedstock load (WWH) of 0.06 to 0.10 h -1 .

[0074] In the present invention, the low-carbon olefin raw materials can be subjected to an ammoxidation reaction in the presence of the catalyst described above to produce nitrile compounds, wherein the low-carbon olefin raw materials are propylene and isobutylene, and the nitrile compounds produced are acrylonitrile and methacrylonitrile.

[0075] In the present invention, the catalyst is used for the ammoxidation reaction of low-carbon olefins to produce nitrile compounds, preferably using propylene, ammonia and air as raw materials for ammoxidation reaction to produce acrylonitrile, wherein the raw material molar ratio is: propylene / ammonia / air = 1 / 1.05-1.3 / 9.2-9.8, the preferred reaction temperature is 420-440°C, the preferred reaction pressure is 0-0.14MPa, and the preferred propylene load (WWH) of the catalyst is 0.06-0.10h -1 .

[0076] The activity evaluation of the catalyst of the present invention was carried out in a fixed bed reactor with an inner diameter of 6 mm. The catalyst loading was 0.5 g, the reaction temperature was 430°C, the molar ratio of propylene / ammonia / air was 1:1.25:9.7, the reaction pressure was atmospheric pressure, and the reaction load (WWH) was 0.085 h -1 Under these conditions, better results were achieved.

[0077] In the present invention, the definitions of propylene conversion, acrylonitrile selectivity and single pass yield are as follows:

[0078]

[0079]

[0080]

[0081] XRD detection conditions, instrument: D8 ADVANCE, CuK α Source, scanning speed 0.5° / min;

[0082] O2-TPO detection conditions, instrument: Bioder PCA-1200S chemical adsorption instrument, catalyst loading 0.08 g, 10% O2 / He flow rate 50 ml / min, heating rate 10℃ / min.

[0083] The present invention is further described below by means of specific examples, but the present invention is not limited by the following examples.

[0084] Example 1

[0085] Weigh 98.5 g (NH4)6Mo7O 24 4H2O

[0086] 105 g of water was added and heated to dissolve to obtain solution (I), in which the molar concentration of Mo ions was 5.0 mol / L.

[0087] 36.4 g of ferric citrate (FeC6H5O7), 18.8 g of oxalic acid dihydrate, 5.2 g of Pr(NO3)3·6H2O and 3.3 g of Nd(NO3)3·6H2O were weighed and added to 40 g of water and heated to dissolve to obtain solution (II), wherein the total molar concentration of Fe, Pr and Nd ions was 3.5 mol / L, and the molar ratio of oxalic acid to Fe ions was 1.0.

[0088] 43.2 g Bi(NO3)3·5H2O, 23.1 g Mg(NO3)2·6H2O, 6.7 g RbNO3, 136.8 g Ni(NO3)2·6H2O and 1.2 g CrO3 were weighed and added to 60 g water and heated to dissolve to obtain solution (III), wherein the total ion molar concentration of Bi, Mg, Rb, Ni and Cr was 5.5 mol / L.

[0089] 172 g of silica sol with a silica content of 40% by weight was weighed and mixed with solution I, and then divided into two parts according to a volume ratio of 1:3, marked as solution I′ and solution I″, respectively, of which the smaller volume was solution I′.

[0090] Solution II and solution I' are mixed to form coprecipitation slurry II', and its pH value is adjusted to 5.0 with dilute ammonia water with a volume concentration of 10%. Solution III and solution I' are mixed to form coprecipitation slurry III'.

[0091] Slurry II' and slurry III' were mixed and stirred, aged at 90°C for 1.0 hour, then dried in an oven at 120°C for 8 hours, and finally calcined at 600°C for 1.5 hours in a muffle furnace containing 0.5% (volume) ammonia in an air atmosphere to obtain a Mo 11.0 Bi 1.8 Fe 2.9 Pr 0.2 Nd 0.1 Mg 1.8 Ni 9.3 R 0.9 Cr 0.2 O x The catalyst comprises 30.0% by weight of the carrier.

[0092] XRD spectrum Figure 1 As shown in the figure, it can be seen that in addition to Fe2(MoO4)3, there is also FeMoO4 phase in the calcined catalyst. Figure 2 As shown in the figure, it can be seen that the calcined catalyst has oxygen consumption peaks at 537°C and 630°C, indicating that there are oxidizable low-valent compounds in the catalyst.

[0093] Example 2

[0094] Weigh 104.7 g (NH4)6Mo7O 24 ·4H2O was added to 150 g of water and heated to dissolve to obtain solution (I), in which the molar concentration of Mo ions was 3.8 mol / L.

[0095] 44.6 g of ferric citrate (FeC6H5O7), 28.7 g of oxalic acid dihydrate and 7.8 g of Nd(NO3)3·6H2O were weighed and added to 66 g of water and heated to dissolve to obtain solution (II), wherein the total molar concentration of Fe and Nd ions was 2.6 mol / L, and the molar ratio of oxalic acid to Fe ions was 1.2.

[0096] 51.7 g Bi(NO3)3·5H2O, 30.2 g Mg(NO3)2·6H2O, 8.9 g RbNO3, 159.2 g Ni(NO3)2·6H2O and 3.5 g Ca(NO3)2·4H2O were weighed and added to 105 g water and heated to dissolve to obtain solution (III). The total molar concentration of Bi, Mg, Rb, Ni and Ca ions was 4.5 mol / L.

[0097] 217 g of silica sol with a silica content of 40% by weight was weighed and mixed with solution I, and then divided into two parts according to a volume ratio of 1:2, marked as solution I′ and solution I″, respectively, of which the smaller volume was solution I′.

[0098] Solution II and solution I' are mixed to form coprecipitation slurry II', and its pH value is adjusted to 3.0 with dilute ammonia water with a volume concentration of 10%. Solution III and solution I' are mixed to form coprecipitation slurry III'.

[0099] Slurry II′ and slurry III′ were mixed and stirred, and then aged at 100° C. for 2 hours, then dried in an oven at 110° C. for 12 hours, and finally calcined at 630° C. for 2 hours in a muffle furnace containing 1.5% (volume) ammonia in an air atmosphere to obtain a slurry having a composition of Mo. 11.0 Bi 2.0 Fe 3.4 Nd 0.3 Mg 2.2 Ni 10.2 R 1.1 Ca 0.3 O x The catalyst contains 32.6% of the carrier by weight.

[0100] The XRD spectrum and O2-TPO diagram are similar to those of Example 1.

[0101] Example 3

[0102] Weigh 89.6 g (NH4)6Mo7O 24·170 g of 4H2O was added and heated to dissolve to obtain solution (I), in which the molar concentration of Mo ions was 2.9 mol / L.

[0103] Weigh 53.6 g of ferric citrate (FeC6H5O7), 38.6 g of oxalic acid dihydrate and 8.9 g of Pr(NO3)3·6H2O, add 80 g of solution and heat to dissolve to obtain solution (II), wherein the total molar concentration of Fe and Pr ions is 2.6 mol / L, and the molar ratio of oxalic acid to Fe ions is 1.4.

[0104] 48.9 g Bi(NO3)3·5H2O, 28.6 g Mg(NO3)2·6H2O, 5.1 g CsNO3, 138.4 g Ni(NO3)2·6H2O, 4.2 g Zr(NO3)4·5H2O and 1.2 g CrO3 were weighed and added to 76 g water and heated to dissolve to obtain solution (III). The molar concentration of the total ions of Bi, Mg, Cs, Ni, Zr and Cr was 4.9 mol / L.

[0105] 295 g of silica sol with a silica content of 30% by weight was weighed and mixed with solution I, and then divided into two equal parts at a volume ratio of 1:1, and marked as solution I′ and solution I″ respectively.

[0106] Solution II and solution I' are mixed to form coprecipitation slurry II', and its pH value is adjusted to 6.5 with dilute ammonia water with a volume concentration of 10%. Solution III and solution I' are mixed to form coprecipitation slurry III'.

[0107] Slurry II' and slurry III' were mixed and stirred, and then aged at 80°C for 3 hours, then dried in an oven at 100°C for 10 hours, and finally calcined at 610°C for 0.5 hours in a muffle furnace containing 2.5% (volume) ammonia in an air atmosphere to obtain a Mo 11.0 Bi 2.2 Fe 4.7 Pr 0.4 Mg 2.4 Ni 10.3 Cs 0.6 Z r0.2 Cr 0.3 O x The catalyst contains 35.1% by weight of the carrier.

[0108] The XRD spectrum and O2-TPO diagram are similar to those of Example 1.

[0109] Example 4

[0110] The method of Example 1 is followed, except that "after mixing the silica sol and solution I, they are divided into two parts according to a volume ratio of 1:3" is replaced by "after mixing the silica sol and solution I, they are divided into two parts according to a volume ratio of 1:4, and the smaller volume is the molybdenum-loaded solution I′", and the other steps are the same as in Example 1.

[0111] The XRD spectrum and O2-TPO diagram are similar to those of Example 1.

[0112] Example 5

[0113] The method of Example 1 is followed, except that "18.8 g of oxalic acid dihydrate" is replaced by "17.5 g of tartaric acid", the molar ratio of tartaric acid to Fe ions is 0.8, and the other steps are the same as in Example 1.

[0114] The XRD spectrum and O2-TPO diagram are similar to those of Example 1.

[0115] Example 6

[0116] The method of Example 1 is followed, except that "aging at 90°C for 1.0 hour" is replaced by "aging at 40°C for 15 minutes", and the other steps are the same as in Example 1.

[0117] The XRD spectrum and O2-TPO diagram are similar to those of Example 1.

[0118] Example 7

[0119] The method of Example 1 is followed, except that the calcination is carried out in an air atmosphere without ammonia, and the other steps are the same as those of Example 1.

[0120] The XRD spectrum and O2-TPO diagram are similar to those of Example 1.

[0121] Comparative Example 1

[0122] The method of Example 1 was followed, except that oxalic acid was not added in step (b), and the pH of the coprecipitated slurry II′ was not adjusted. The other steps were the same as in Example 1. Figure 2 As shown in the figure, it can be seen that there is no obvious oxygen consumption peak around 530℃ and 600℃, indicating that there are fewer low-valent compounds in the catalyst that can be oxidized.

[0123] Comparative Example 2

[0124] The method of Example 1 is followed, except that the molybdenum-loaded solution is not divided into two parts, oxalic acid is not added in step (b), all solutions are directly mixed to form a coprecipitation slurry, and the coprecipitation slurry is not pH-adjusted, and is calcined in an air atmosphere. The other steps and treatment conditions are the same as in Example 1. The O2-TPO diagram is shown in FIG. Figure 2As shown in the figure, it can be seen that there is no obvious oxygen consumption peak around 530℃ and 600℃, indicating that there are fewer low-valent compounds in the catalyst that can be oxidized.

[0125] The catalysts prepared in the examples and comparative examples were used to perform ammoxidation of propylene to produce acrylonitrile under the following reaction conditions. The results are shown in Table 1.

[0126] φ6 mm fixed bed reactor

[0127] Reaction temperature 430℃

[0128] Reaction pressure: normal pressure

[0129] Catalyst loading 0.5 g

[0130] Catalyst propylene load (WWH) 0.085h -1

[0131] Raw material ratio (molar): propylene / ammonia / air = 1 / 1.25 / 9.7

[0132] Table 1

[0133]

[0134]

[0135] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A catalyst containing divalent iron, characterized in that: The catalyst comprises a carrier and an active component represented by the following general formula: Mo 11.0 Bi b Feb c D d HAVE BEEN e F f O x , wherein D is selected from at least one of Li, Na, K, Rb and Cs; E is at least one selected from the group consisting of rare earth elements La, Pr, Nd, Sm and Eu; F is selected from at least one of Ca, Mg, Zr, Te, Sb, Ni, Cr, W and Nb; in, b is in the range of 0.1 to 5.0; c is in the range of 0.1 to 5.0; d is in the range of 0.1 to 5.0; e is in the range of 0.1 to 5.0; f is in the range of 0.1 to 15.0; x is the total number of oxygen atoms required to satisfy the valence of each element in the catalyst; There is a divalent iron phase in the catalyst crystal structure.

2. The catalyst according to claim 1, wherein The carrier accounts for 30-65% of the weight of the catalyst and the active component accounts for 35-70% of the weight of the catalyst, calculated as oxide; and / or In the catalyst, there are low-valent compounds that can be oxidized.

3. The method for preparing a divalent iron-containing catalyst according to claim 1 or 2, characterized in that: The method includes: (a) dissolving a Mo source to obtain a molybdenum-containing solution I; (b) dissolving the Fe source, the organic acid additive and the E source to obtain an iron-containing solution II; (c) dissolving the remaining active component sources to obtain active component solution III; (d) mixing a required amount of carrier source with molybdenum-containing solution I and dividing the mixture into two parts by volume, labeled as molybdenum-containing solution I′ and molybdenum-containing solution I″; (e) mixing the iron-containing solution II with the molybdenum-carrying solution I′ to form a coprecipitation slurry II′, controlling the coprecipitation The pH value of slurry II' is 1.0-8.0; the active component solution III and the molybdenum-carrying solution I" are mixed to form a coprecipitation slurry III'; (f) The coprecipitation slurry II′ and the coprecipitation slurry III′ are then mixed and aged, and then dried and calcined to obtain a catalyst.

4. The preparation method according to claim 3, wherein The volume ratio of the molybdenum-carrying solution I′ to the molybdenum-carrying solution I″ is 1:0.5-5, preferably 1:1-3.

5. The preparation method according to claim 3 or 4, wherein In step (b), The organic acid adjuvant is one or more of tartaric acid, citric acid and oxalic acid, preferably oxalic acid, more preferably oxalic acid dihydrate; and / or The molar ratio of the organic acid additive to the Fe ions in the iron source is 0.5 to 5.0, preferably 1.0 to 2.

5.

6. The preparation method according to any one of claims 3 to 5, wherein: In step (b), the Fe source is one or more of ferric nitrate, ferric sulfate, and ferric citrate, preferably ferric citrate.

7. The preparation method according to any one of claims 3 to 6, wherein: In step (e), The alkaline substance is an inorganic base, preferably one or more of sodium hydroxide, potassium hydroxide, and ammonia water, more preferably ammonia water; The pH value of the coprecipitation slurry II' is 3.0 to 7.

0.

8. The preparation method according to any one of claims 3 to 7, wherein: In step (f), The aging conditions include: a temperature of 40 to 150°C, preferably 50 to 120°C; and / or The time is 10 minutes to 10.0 hours, preferably 30 minutes to 5.0 hours.

9. The preparation method according to any one of claims 3 to 8, wherein: In step (f), Drying conditions include: a temperature of 80 to 160°C, preferably 90 to 150°C; The time is 5.0 to 24.0 hours, preferably 8.0 to 12.0 hours.

10. The preparation method according to any one of claims 3 to 9, wherein: In step (f), the calcination conditions include: the calcination environment adopts an air atmosphere, or a mixed atmosphere of a trace amount of reducing gas and air, wherein; preferably, in the mixed atmosphere, the volume percentage of the reducing gas is 0.01 to 3.0%, preferably 0.5 to 2.5%, and the reducing gas is preferably ammonia; The calcination temperature is 550-650°C, and the calcination time is 30 minutes to 2.5 hours.

11. The preparation method according to any one of claims 3 to 10, wherein: The Mo concentration of the molybdenum-containing solution I is 2.0 to 8.0 mol / L, preferably 2.5 to 5.5 mol / L; and / or The total metal ion concentration of the iron-containing solution II is 1.0 to 5.0 mol / L, preferably 2.5 to 4.2 mol / L; and / or The total metal ion concentration of the active component solution III is 3.0 to 14.0 mol / L, preferably 4.0 to 6.0 mol / L; and / or The carrier source is selected from silica sol, wherein the weight content of silicon dioxide is 25-50%, preferably 30-40%.

12. Use of the catalyst according to claim 1 or 2 in an ammoxidation reaction, preferably in an ammoxidation reaction of a lower carbon olefin, more preferably the lower carbon olefin is propylene and / or isobutylene.

13. A method for producing nitrile compounds by ammoxidation of light olefins, characterized in that: The method comprises: carrying out an ammoxidation reaction with low-carbon olefins, ammonia and air as raw materials; wherein, preferably, The raw material molar ratio is: propylene / ammonia / air = 1: (1.05-1.3): (9.2-9.8); and / or The reaction temperature is 420-440°C; and / or The reaction pressure is 0 to 0.14 MPa; and / or The olefin feedstock loading (WWH) of the catalyst is 0.06~0.10h -1 .

Citation Information

Patent Citations

  • Iron spinel composite oxide catalyst and application thereof

    CN104437577A

  • Acrylonitrile catalyst for propylene ammoxidation process

    CN107398285A

  • Molten iron catalyst and preparation method and application thereof

    CN111822026A

  • Ammonia oxidation catalyst, preparation method thereof and method for preparing acrylonitrile by using ammonia oxidation catalyst

    CN116322994A

  • Catalyst for fluidized bed ammoxidation reaction, and method for producing acrylonitrile

    US20190001309A1